Analysis Of The Form Of Sustainable Fashion And The Quality Of Disclosure Of Economic, Social And Environmental Aspects On The Website In 2022: A Case Study Of Sukkhacitta.Com - Tania, Lina; Meiden, Carmel (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2024)
In this era of Globalization, the world's population has increased so human needs and desires must also continue to grow. Choosing needs, cannot be separated from a person's lifestyle, where fashion has become an inseparable part of daily appearance and style. The development of the fashion industry is in line with fashion which is no longer just a necessity but also a lifestyle. This research is the result of practice-based research, where local brand SukkhaCitta strives to design sustainable fashion collections by raising the issue of clothes that can heal the earth. Through this practice, Sukkhacitta retraces the footsteps of their ancestors, where SukkhaCitta makes clothes directly manually in the village without using factories.  From the application of traditional agroforestry to spices used as natural pesticides. Intercropping naturally balances the carbon cycle between the soil and the atmosphere. Another attraction that SukkhaCitta tries to highlight is the storytelling behind each product it makes. This story element is what differentiates SukkhaCitta from other fast fashion products that only follow trends.